Quality of life among cancer inpatients 80 years and older: a systematic review - Drageset, Jorunn (Health Qual Life Outcomes, 2021)
OBJECTIVE: The aim of this systematic review was to summarize and assess the literature on quality of life (QoL) among cancer patients 80 years and older admitted to hospitals and what QoL instruments have been used. METHODS: We searched systematically in Medline, Embase and Cinahl. Eligibility criteria included studies with any design measuring QoL among cancer patients 80 years and older hospitalized for treatment (surgery, chemotherapy or radiation therapy). Exclusion criteria: studies not available in English, French, German or Spanish. We screened the titles and abstracts according to a predefined set of inclusion criteria. All the included studies were assessed according to the Critical Appraisal Skills Programme checklists, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement checklist was used to ensure rigor in conducting and reporting. This systematic review was registered in PROSPERO (CRD42017058290). RESULTS: We included 17 studies with 2005 participants with various cancer diagnoses and Classification of Malignant Tumors stages (TNM). The included studies used a range of different QoL instruments and had different aims and outcomes. Both cancer-specific and generic instruments were used. Only one of the 17 studies used an age-specific instrument. All the studies included patients 80 years and older in their cohort, but none specifically analyzed QoL outcomes in this particular subgroup. Based on findings in the age-heterogeneous population (age range 20–100 years), QoL seems to be correlated with the type of diagnosed carcinoma, length of stay, depression and severe symptom burden. CONCLUSION: We were unable to find any research directly exploring QoL and its determinants among cancer patients 80 years and older since none of the included studies presented specific analysis of data in this particular age subgroup. This finding represents a major gap in the knowledge base in this patient group. Based on this finding, we strongly recommend future studies that include this increasingly important and challenging patient group to use valid age- and diagnosis-specific QoL instruments.